Cross-cultural design : applications in health, learning, communication, and creativity : 12th International Conference, CCD 2020, held as part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings, Part II /: applications in health, learning, communication, and creativity : 12th International Conference, CCD 2020, held as part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings, Part II. ([2020]) - Unknown
No abstract available